Prevalence of domestic violence during pregnancy in a Turkish community - Deveci, S. Erhan; Acik, Yasemin; Gulbayrak, Canan; Tokdemlr, Mehmet; Ayar, Ahmet (SEAMEO TROPMED Network, 2007)
This study was carried out to determine the prevalence and risk factors for domestic violence victimization of women during pregnancy by intimate partner throughout marriage In a Turkish community. Pregnant women living in the servicing area of selected health centers in Elazlg were considered for the study and data were obtained through a questionnaire. A total of 249 pregnant women, mean age 26.8 ±5.2 years and the mean gravidity 2.6 ±1.7, were involved. Of the 249 women, 28.9% were exposed to at least one case of physical violence throughout matrimony, 12.4% being abused during the previous year and 4.8% during the current pregnancy, 30.5% were exposed to verbal insult and 4.4% exposed to sexual abuse during the current pregnancy, In addition, 25.7% were exposed to one or more types of domestic violence during previous pregnancies. There was a significant correlation between the rate of violent victimization and number of children, and the partner's alcohol habits and socioeconomical status of the families (p < 0.05). Results from the self-report of the receiving end of violent behaviors indicate that the rates of any type of intimate partner violence were very high among pregnant women in this studied Turkish population, Efforts to reduce the incidence of this women's rights and public health problem should be given high priority.